Ultrasonographic diagnosis of splenic torsion: a case report - Di, Zhiyan; Zhao, Shasha (Frontiers in Surgery, 2025)
We report an exceptional case of 900° splenic-torsion with accessory spleen in a 17-month-old girl presenting with nonspecific vomiting and fever. Initial CT suggested an abdominal mass, ultrasonography definitively diagnosed splenic torsion through characteristic findings: absent parenchymal flow, twisted hilar vessels (“whirlpool sign”), and preserved accessory spleen perfusion. This case highlights ultrasound's superior diagnostic capability over CT for pediatric splenic torsion, particularly in demonstrating dynamic vascular compromise. The report emphasizes key sonographic criteria and the critical 6-hour window for salvageable splenic ischemia.